Feature article: δ-Aminolevulinate induces fetal hemoglobin expression by enhancing cellular heme biosynthesis. Issue 14 (October 2019) - Liu, Li; Zhu, Xingguo; Yu, Alexander; Ward, Christina M; Pace, Betty S
Sickle cell disease (SCD) and β-thalassemia are inherited blood disorders caused by genetic defects in the β-globin gene on chromosome 11, producing severe disease in people worldwide. Induction of fetal hemoglobin consisting of two α-globin and two γ-globin chains ameliorates the clinical symptoms of both disorders. In the present study, we investigated the ability of δ-aminolevulinate (ALA), the heme precursor, to activate γ-globin gene expression as well as its effects on cellular functions in erythroid cell systems. We demonstrated that ALA induced γ-globin expression at both the transcriptional and protein levels in the KU812 erythroid cell line. Using inhibitors targeting two enzymes in the heme biosynthesis pathway, we showed that cellular heme biosynthesis was involved in ALA-mediated γ-globin activation. Moreover, the transcription factor NRF2 (nuclear factor [erythroid-derived 2]-like 2), a critical regulator of the cellular antioxidant response, was activated by ALA and contributed to mechanisms of γ-globin activation; ALA did not affect cell proliferation and was not toxic to cells. Subsequent studies demonstrated ALA-induced γ-globin activation in erythroid progenitors generated from normal human CD34 + stem cells. These data support future study to explore the potential of stimulating intracellular heme biosynthesis by ALA or similar compounds as a novel therapeutic strategy for treating SCD and β-thalassemia. Impact statement: Inherited mutations in the β-globin-like genes result in the most common forms of genetic blood disease including sickle cell disease (SCD) and β-thalassemia worldwide. Therefore, effective inexpensive therapies that can be distributed widely are highly desirable. Currently, drug-mediated fetal hemoglobin (HbF) induction can ameliorate clinical symptoms of SCD and β-thalassemia and is the most effective strategy for developing new therapeutic options. In the current study, we confirmed that δ-Aminolevulinate (ALA), the precursor of heme, induces γ-globin expression at both the transcriptional and translational levels in primary human erythroid progenitors. Moreover, the results indicate activation of the transcription factor NRF2 (nuclear factor (erythroid-derived 2)-like 2) by ALA to enhance HbF expression. These data support future study to explore the potential of stimulating intracellular heme biosynthesis by ALA or similar compounds as a novel therapeutic strategy for treating SCD and β-thalassemia.